(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Electronic payment methods are considered one of the most important topics in the financial and banking industry, as they contribute to contemporary developments in providing digital banking services and diversifying bank channels and branches in multiple geographical locations, which helped attract customers. Accordingly, the research aims to analyze the application of electronic payment methods and their role in enhancing Banking return, As for the importance, it appears by referring to the electronic payment methods used in banks, as they are a powerful tool for improving the competitiveness of banks and explaining the risks and challenges facing their application, The International Development Bank was chosen as a research sample due to the availability of its financial data, and mathematical equations were used to measure banking return indicators, The application of electronic payment methods was verified based on the bank’s annual reports for the period specified for the research, The Excel program was also used to extract the results. The study reached a number of results that were very important, including that the use of electronic payment methods can affect banks’ returns in a varying manner, but sometimes the effect is weak. As for the most important recommendations, each bank must carefully study the impact of using electronic payment methods on its returns, and government and regulatory policies must support and encourage the use of financial technology in a way that enhances the economy and the stability of the financial system.